Written feedback on ESL student writers’ academic essays - Tee, Kelly Pei Leng; Kumar, Vijay; Abdullah, Mardziah Hayati (Universiti Putra Malaysia Press, 2013)
This paper provides an analysis of written feedback on ESL student writers’ academic essays to shed light on how feedback acts as a communicative tool between the lecturer and students. The objective of this study is to explore the types and usefulness of written feedback on ESL student writers’ academic writing. First, it discusses the importance of feedback and the theoretical framework of the Speech Act Theory. The data for this study comprises written feedback and students’ interviews. The feedback was coded, and a model for analysis was developed based on two primary roles of speech: directive and expressive. Based on this analysis, the paper discusses the types of feedback from which students benefit the most, namely, directive-instruction feedback and expressive-disapproval feedback. The interview conducted as part of this study provided insightson how the students felt about each type of feedback. This study also suggests a possibility of developing a taxonomy of good feedback practices by considering the views of the giver and receiver of written feedback.